Anerkennungs- und Missachtungskulturen von Mädchen und Jungen im Sportunterricht - Grimminger-Seidensticker, Elke (Geschlecht und bewegungsbezogene Bildung(sforschung))

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Virtual tester development using HDL/PLI - Kamran, Arezoo; Nemati, Nastaran; Sadeghi-Kohan, Somayeh; Navabi, Zainalabedin (2010 East-West Design & Test Symposium (EWDTS))

Synthesis of highly stable magnesium fluoride suspensions and their application in the corrosion protection of a Magnesium alloy - Waltz, Florian; Swider, Mark A.; Hoyer, Kay-Peter; Hassel, Thomas; Erne, Martin; Möhwald, Kai; Adlung, Matthias; Feldhoff, Armin; Wickleder, Claudia; Bach, Friedrich-Wilhelm; Behrens, Peter (Journal of Materials Science)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

The ‘German Nation’ and the ‘black Other’: Social Darwinism and the cultural mission in German colonial discourse - Schubert, Michael (Patterns of Prejudice)

French, Belgian, British and US Occupation Troops in Western and Southwestern Germany 1918-1930 - Schubert, Michael (The Encyclopedia of Migration and Minorities in Europe. From the 17th Century to the Present)

(the ActiFE Study Group). Walking on sunshine: effect of weather conditions on physical activity in older people - Klenk, J.; Büchele, G.; Rapp, K.; Franke, Sebastian; Peter, R. (Journal of Epidemiology and Community Health. JECH Online First, published on February 15, 2011)

Assessing the long-term effect of industrial services on firm profitability: The moderating impact of product innovations (ausgezeichnet mit Best Overall Conference Paper Award) - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (2011 AMA Winter Academic Conference, Austin, TX)

Service orientation of manufacturing companies: A necessary or sufficient condition for firm profitability? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (40th EMAC Annual Conference, Ljubljana)

Time extension of sales promotions – How do customers react? - Münkhoff, Eva; Garnefeld, I.; Bruns, A. (40th EMAC Annual Conference, Ljubljana)